2020
DOI: 10.1101/2020.12.27.424483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and functional properties of PFC astrocytes during neuroinflammation-induced anhedonia

Abstract: Astrocytes are widely implicated in CNS diseases, but their contributions to disease related phenotypes remain incompletely explored. Anhedonia accompanies several neurological and psychiatric diseases, including major depressive disorder (MDD) and Alzheimer’s disease (AD), both of which are associated with neuroinflammation. In order to explore how neuroinflammation affects astrocytes, we assessed medial prefrontal cortex (PFC) and visual cortex (VCX) astrocytic gene expression using a neuroinflammation mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(103 reference statements)
1
5
0
Order By: Relevance
“…Akin to previous studies, results from the current study showed that RiboTag can be used as an effective method to isolate astrocyte-specific mRNAs for subsequent RNA-seq (Boisvert et al, 2018;Yu et al, 2021;Diaz-Castro et al, 2021), which can be used to elucidate cell-type specific transcriptional and translational changes. We hypothesized that cocaine-administering rats would display significant numbers of differentially expressed genes in comparison to saline at both withdrawal timepoints, day 1 and 45.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Akin to previous studies, results from the current study showed that RiboTag can be used as an effective method to isolate astrocyte-specific mRNAs for subsequent RNA-seq (Boisvert et al, 2018;Yu et al, 2021;Diaz-Castro et al, 2021), which can be used to elucidate cell-type specific transcriptional and translational changes. We hypothesized that cocaine-administering rats would display significant numbers of differentially expressed genes in comparison to saline at both withdrawal timepoints, day 1 and 45.…”
Section: Discussionsupporting
confidence: 57%
“…Following diffusion, microinjectors were removed slowly over 1-2 minutes. Plasmids for AAV manufacturing used were pZac2.1.GfaABC1D-Rpl22-HA (Diaz-Castro et al, 2019;Diaz-Castro et al, 2021;Yu et al, 2020). The plasmid was provided by Addgene and packaged into an AAV at the UNC Viral Vector Core.…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose LPS to induce a physiological form of systemic inflammation. LPS produces robust and pervasive inflammation, including microglial and astrocytic activation within the CNS (Hoogland et al, 2015;Perez-Dominguez et al, 2019;Diaz-Castro et al, 2021). In particular, LPS was previously shown to cause the secretion of pro-inflammatory mediators and neuronal activation within the LPBN (Tkacs and Li, 1999;Zhang et al, 2003;Cheng et al, 2022).…”
Section: Failed To Induce Any Detectable Changes In Lpbn Glial Cellsmentioning
confidence: 99%
“…Despite the clear evidence that glial cells of peripheral somatosensory system, including dorsal root ganglion (DRG) and spinal cord, play a pivotal role in sensory perception, processing as well as motor behavior, their cellular and functional heterogeneity remain unclear. Recently, emerging evidence has revealed cellular and molecular heterogeneity in specific glial cells of the CNS using single-cell (scRNA-seq) or single-nucleus RNA sequencing (snRNA-seq) [3,[9][10][11][12]. Using scRNA-seq, Hasel et al identified 10 astrocyte subclusters in the mouse brain and characterized the heterogeneous responses of different astrocyte subsets to inflammation [12].…”
Section: Introductionmentioning
confidence: 99%